2006
DOI: 10.1021/es052407f
|View full text |Cite
|
Sign up to set email alerts
|

Compound Class Specific 14C Analysis of Polycyclic Aromatic Hydrocarbons Associated with PM10 and PM1.1 Aerosols from Residential Areas of Suburban Tokyo

Abstract: Compound class specific radiocarbon analysis (CCSRA) was performed for polycyclic aromatic hydrocarbons (PAHs) associated with airborne particulate matter (APM) with diameter <10 microm (PM10) and <1.1 microm (PM1.1) collected from a residential area of suburban Tokyo, Japan, and seasonal and particle-size radiocarbon variations were investigated. Source diagnostic isomer pair ratios indicated mixed contributions from petroleum combustion and from biomass and coal combustion to the PAHs in APM. The delta14C- P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 27 publications
3
60
2
1
Order By: Relevance
“…For other emission sources, contributions of biomass burning, for example, can be higher. Kumata et al (2006) elucidated that the contribution of biomass burning was several tens of percent to the total atmospheric aerosols even in the urban area (Tokyo metropolitan area). On the other hand, for nitro-PAHs, especially for 1-NP, the formation of the nitro derivatives would be lower for biomass burning, and the major sources of nitro-PAHs can reasonably be assumed to be from diesel vehicle emissions (Tang et al 2005).…”
Section: Comparison Between Atmospheric Emission and Sedimentation Lomentioning
confidence: 99%
“…For other emission sources, contributions of biomass burning, for example, can be higher. Kumata et al (2006) elucidated that the contribution of biomass burning was several tens of percent to the total atmospheric aerosols even in the urban area (Tokyo metropolitan area). On the other hand, for nitro-PAHs, especially for 1-NP, the formation of the nitro derivatives would be lower for biomass burning, and the major sources of nitro-PAHs can reasonably be assumed to be from diesel vehicle emissions (Tang et al 2005).…”
Section: Comparison Between Atmospheric Emission and Sedimentation Lomentioning
confidence: 99%
“…For bulk carbon, contemporary sources can include both biogenic emission and biomass combustion sources, so these results can only be used to define contribution of fossil fuel combustion sources including motor vehicles and power generation. Advances in molecular-level radiocarbon analysis (Eglinton et al, 1996) have allowed compound class-specific radiocarbon analysis (CCSRA) of atmospheric PAHs (Mandalakis et al, 2005;Zencak et al, 2007b;Kumata et al, 2006). These studies have revealed geographic differences in fossil vs. modern biomass sources of PAH across Europe and in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed geographic differences in fossil vs. modern biomass sources of PAH across Europe and in Japan. The study from Japan is compelling as it indicates the importance of isolating individual PAHs for compound-specific radiocarbon analysis (CSRA) by revealing differences in the contribution from biomass burning between pooled low versus high molecular weight PAHs (Kumata et al, 2006). These results combined with emission source profiles suggest that source contributions would not be uniform for all PAHs.…”
Section: Introductionmentioning
confidence: 99%
“…After dispersion, PAHs accumulate on ground surfaces and discharge into water bodies with rain. The behavior of PAHs has been extensively studied in atmospheric and aquatic environments (Takada et al, 1990;Baek et al, 1991;Sharma et al, 1994;Lee et al, 1995;Wan et al, 2006;Kumata et al, 2006). Still, the relation of the source and environmental fate has not been well clarified yet.…”
mentioning
confidence: 99%